2014
DOI: 10.1038/modpathol.2013.235
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma gene mutations detected by whole exome sequencing of Merkel cell carcinoma

Abstract: Merkel cell carcinoma is a highly aggressive cutaneous neuroendocrine tumor that has been associated with Merkel cell polyomavirus in up to 80% of cases. Merkel cell polyomavirus is believed to influence pathogenesis, at least in part, through expression of the large T antigen, which includes a retinoblastoma protein-binding domain. However, there appears to be significant clinical and morphological overlap between polyomaviruspositive and polyomavirus-negative Merkel cell carcinoma cases. Although much of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 51 publications
(68 reference statements)
8
49
1
3
Order By: Relevance
“…MCPyV is a DNA virus that likely mediates tumorigenesis via large T antigen (LTAg) binding to the tumor suppressor RB1 and small T antigen (sTAg) upregulation of oncoprotein stability and mTOR activation (1,2). Unlike MCPyV-positive tumors, MCPyV-negative MCC tumors display high mutation burdens, TP53 and RB1 mutations, and UV-signature mutational profiles, suggesting a molecular dichotomy between MCPyV-positive and MCPyV-negative tumors that may have translational relevance (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…MCPyV is a DNA virus that likely mediates tumorigenesis via large T antigen (LTAg) binding to the tumor suppressor RB1 and small T antigen (sTAg) upregulation of oncoprotein stability and mTOR activation (1,2). Unlike MCPyV-positive tumors, MCPyV-negative MCC tumors display high mutation burdens, TP53 and RB1 mutations, and UV-signature mutational profiles, suggesting a molecular dichotomy between MCPyV-positive and MCPyV-negative tumors that may have translational relevance (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…31 Merkel cell carcinoma with squamous elements or coexisting squamous cell carcinoma is often Merkel cell polyomavirus negative. 12,23,25,[33][34][35][36] Recent findings indicate that Merkel cell polyomavirusnegative tumors may be associated with RB1 inactivating mutations 37 and (in a subset) PIK3CA activating mutations. 38 Hence, although additional study is needed to clarify differences between Merkel cell polyomavirus-positive and Merkel cell polyomavirus-negative tumors, current data suggest that molecular differences exist that may have implications for immune-based or targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Within virus-positive tumors, several groups have demonstrated non-recurrent clonal integration of the virus into the host genome, where a mutated viral large T antigen (LTA) is expressed that binds to and induces a conformational change in RB1 interfering with its cell cycle regulation (Angermeyer et al, 2013;Chang and Moore, 2012;Cheng et al, 2013;Demetriou et al, 2012;Houben et al, 2012Houben et al, , 2010Sastre-Garau et al, 2009;Shuda et al, 2008;Sihto et al, 2011). Recently, Cimino et al (2014) demonstrated by whole exome sequencing in a small cohort of 3 cases in our laboratory that MCPyV-negative Merkel cell carcinomas have protein truncating mutations in RB1 (Cimino et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…One distinguishing feature, however, is that while up to 80% of Merkel cell carcinomas harbor the Merkel cell polyomavirus (MCPyV), the virus appears to be absent or rare in salivary high-grade NECs, including those of the 'Merkel cell type' (Chernock et al, 2011;de Biase et al, 2012;Duncavage et al, 2009;Ellis and Auclair, 2008;Feng et al, 2008). Retinoblastoma protein 1 (RB1) inactivation appears to be important in the pathogenesis of both MCPyV-positive and MCPyV-negative Merkel cell carcinomas (Cimino et al, 2014). Within virus-positive tumors, several groups have demonstrated non-recurrent clonal integration of the virus into the host genome, where a mutated viral large T antigen (LTA) is expressed that binds to and induces a conformational change in RB1 interfering with its cell cycle regulation (Angermeyer et al, 2013;Chang and Moore, 2012;Cheng et al, 2013;Demetriou et al, 2012;Houben et al, 2012Houben et al, , 2010Sastre-Garau et al, 2009;Shuda et al, 2008;Sihto et al, 2011).…”
Section: Introductionmentioning
confidence: 97%